The Role of Supply Chain Capability as Mediation Between Digitalization and Digital Connectivity on Operational Performance - Aulia Fariha Fauzi, Putri; Hendayani, Ratih; Iskamto, Dedi (Riviera Publishing, 2023)
The purpose of this study was to identify the factors that influence the operational performance of PT. Kereta Api Indonesia (Persero) or PT.KAI at Head Office in Indonesia using IPMA analysis on SmartPLS. This research develops theoretical aspects of understanding digitalization in Indonesia, which consists of supply chain capability variables mediating between digitalization and digital connectivity. Additionally, the study explores the roles of digital culture and technological turbulence as moderators influencing operational performance. Then, there is digital connectivity that will affect operational performance. This study uses a quantitative method with data sources derived from surveys through the distribution of online questionnaires to 48 Employees in the Logistics Department. The data analysis technique used is SEM-PLS and IPMA Analysis using SmartPLS software. Digitalization exhibits the greatest impact on operational performance in the presence of a mediating variable, which is the supply chain capability of PT. As supported by the IPMA analysis, KAI (Persero) at the Head Office indicates that digitalization holds the highest performance value compared to other variables—the management of PT. KAI must focus on digital culture, supply chain capability, and technological turbulence in conjunction with digitalization. This approach is crucial to ensure the company implements the Rapid Apps and maintains operational performance consistently. The study is the first study conducted to analyze the factors that influence operational performance in PT. KAI, so that it can be a reference and additional reference on academic knowledge and managerial aspects.